UNPROCESSED NUTRITION: BIOCHEMICAL MECHANISMS, HEALTH BENEFITS, AND THERAPEUTIC POTENTIAL (Journal of Medical & Health Sciences Review, 2025)
The intensity of lifestyle disease-driven global health crises leads to the adoption of unprocessed nutrition which bases itself on scientific models of biochemical integrity and evolutionary dietary traces. The review analyzes how unprocessed food benefits our bodies by maintaining phytonutrients and enzymes with their original activity as well as preserving the molecular structure of food. Dietary fiber together with polyphenols and bioactive peptides generate a synergistic effect that regulates key signaling pathways becoming influential through their actions on NF-κB and AMPK and SIRT1 pathways. The fields of metabolomics and nutrigenomics and next-generation sequencing technology have transformed our comprehension of unprocessed food impacts on gene expression along with redox stability and gastrointestinal microbe communities. Research involving CRISPR-based microbiome editing and multi-omics data combination has shown how individual reactions to unprocessed food diets affect non-communicable diseases like metabolic syndrome and neuro-inflammation and gut dysbiosis. Researchers use machine learning methods to determine dietary outcomes while identifying population groups through metabolic reactions after consuming unprocessed food. This paper evaluates existing research to promote a systems biology strategy for unprocessed nutrition by showing its value for disease prevention together with its potential as precision nutrition-based therapeutic applications. Upcoming integrative health plans will use unprocessed nutrition as their central guiding principle due to biochemical knowledge and technological development.